THE CATEGORIZATION OF ENGLISH CONSONANT SOUNDS (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article provides an in-depth exploration of English consonant classification, breaking down the complexities of speech sounds into three main categories: place of articulation, manner of articulation, and voicing. It explains how consonants are formed by manipulating airflow and highlights the roles of various speech organs, such as the tongue, lips, and vocal cords. Special attention is given to unique features of English consonants, including aspiration, flapping, and dark /l/, which illustrate the richness and diversity of